2006
DOI: 10.1111/j.1745-7254.2006.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and effect of para-toluene-sulfonamide on rat liver microsomal cytochrome P450 from in vivo and in vitro studies

Abstract: Aim: To study the in vivo and in vitro metabolism and the effect of para-toluenesulfonamide (PTS) on cytochrome P450 enzymes (CYP450). Methods: Total CYP450 and microsome protein content were determined after iv pretreatment of rats with PTS. CYP-specific substrates were incubated with rat liver microsomes. Specific CYP isoform activities were determined by using HPLC. CYP chemical inhibitors added to the incubation mixture were used to investigate the principal CYP isoforms involved in PTS metabolism. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The effects of several human selective P450 inhibitors on the formation of the Phase I metabolites M1 and M2 in rat liver microsomes were investigated. The inhibitors used were: α‐naphthoflavone (for CYP1A),17 quinidine (for CYP2D1),18 orphenadrine (for CYP2B),19, 20 diethyldithiocarbamate (for CYP2E1),21 sulfaphenazole (for CYP2C6/11),22 and ketoconazole (for CYP3A1/2) 23. The concentrations used for BBR were 10, 50, and 200 µM and the concentrations of various inhibitors used were 2 and 10 µM for quinidine, 1 and 10 µM for α‐naphthoflavone, 10 and 50 µM for sulfaphenazole, 25 and 50 µM for orphenadrine, 12.5 and 25 µM for diethyldithiocarbamate, 1 and 10 µM for ketoconazole.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of several human selective P450 inhibitors on the formation of the Phase I metabolites M1 and M2 in rat liver microsomes were investigated. The inhibitors used were: α‐naphthoflavone (for CYP1A),17 quinidine (for CYP2D1),18 orphenadrine (for CYP2B),19, 20 diethyldithiocarbamate (for CYP2E1),21 sulfaphenazole (for CYP2C6/11),22 and ketoconazole (for CYP3A1/2) 23. The concentrations used for BBR were 10, 50, and 200 µM and the concentrations of various inhibitors used were 2 and 10 µM for quinidine, 1 and 10 µM for α‐naphthoflavone, 10 and 50 µM for sulfaphenazole, 25 and 50 µM for orphenadrine, 12.5 and 25 µM for diethyldithiocarbamate, 1 and 10 µM for ketoconazole.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in dogs suggested a similar metabolic pathway; 4-sulphamoylbenzoic acid was found in the urine of dogs given p-toluenesulfonamide 22 . Following intravenous administration of 33 or 198 mg/kg p-toluenesulfonamide to male Wistar rats for 4 days, total cytochrome P450 content in control and treated animals was similar 23 . The authors demonstrated that p-toluenesulfonamide metabolism is likely mediated through CYP2C7, CYP2D1, and CYP3A2.…”
Section: Absorption Distribution Metabolism Excretion and Toxicokmentioning
confidence: 84%
“…Measurement of intracellular PST by high-performance liquid chromatography (HPLC) was performed as described previously 9 . HPLC was performed using an Agilent 1100LC system (Agilent Technologies, Palo Alto, California, USA) equipped with a Zorbax C8 column (4.6×250 mm, 5 μm; Dupont, Wilmington, Delaware, USA).…”
Section: Methodsmentioning
confidence: 99%